Intelligent wheeled mobile robot navigation - Mester, Gyula (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
The paper deals with the wireless sensor-based remote control of mobile robots motion in an unknown environment with obstacles using the Sun SPOT technology and gives the fuzzy velocity control of a mobile robot motion in an unknown environment with obstacles. When the vehicle is moving towards the target and the sensors detect an obstacle, an avoiding strategy and velocity control are necessary. We proposed the wireless sensor-based remote control of mobile robots motion in an unknown environment with obstacles using the Sun SPOT technology and a fuzzy reactive navigation strategy of collision-free motion and velocity control in an unknown environment with obstacles. The simulation results show the effectiveness and the validity of the obstacle avoidance behavior in an unknown environment. The proposed method have been implemented on the miniature mobile robot Khepera® that is equipped with sensors.